COMPARE THE EFFECTIVENESS OF CONSTRAINT INDUCED MOVEMENT THERAPY AND MOTOR RELEARNING PROGRAMME IN POST STROKE PATIENTS - Maratis, Jerry; Wahidin, Ahmad; Ivanali, Kesit (Universitas Muhammadiyah Surakarta, 2021)
Objective: Compare the effectiveness of Constraint Induced Movement Therapy (CIMT) and Motor Relearning Program (MRP) on upper extremity and hand functions in post-stroke patients.. Methods: This research is an experimental study design. randomaized control pre test post-Test Design. Sample of convenience of twelve (12) stroke subjects are selected and devided into group I and group II. Group I received CIMT and group II with MRP. Results: test normality with Shapiro Wilk Test obtained normal distribution data while with test homogenity with Levene's test obtained data has variant Homogen. The results of hypothesis testing in treatment group I with the One Sampels T-test obtained pvalue <0.001 in Wolf Motor Function Test (WMFT) CIMT intervention can improve Upper Etremity function. In the treatment group II with the One Sampels T-test, the pvalue was <0.001 at WMFT. So it can be concluded that MRP intervention can improve Upper Extremity function. The independent sample t-test results show a p-value <0.360, which means there is no difference in the functional increase in Upper Extremity Stroke conditions between CIMT and MRP interventions. Conclusion: there was no difference in effectiveness between CIMT and MRP for improving upper extremity function in poststroke patients.